Flying high : - Wynbrandt, James (Wiley, 2004)
As the founder by the age of 40 of three successful discount airline companies-most recently the billion-dollar JetBlue-David Neeleman and his story deserves in-depth analysis. Unfortunately, this largely uncritical profile doesn’t provide that. Veteran aviation and business writer Wynbrandt presents Neeleman’s life in a lively and highly readable style. The first half lays out the details of Neeleman’s major successes: turning the small leisure business Morris Travel into a national air charter by developing the concept of ticketless reservations, which Wynbrandt correctly claims "would forever revolutionize airline bookings," and brokering a deal with Southwest Airlines, which purchased Morris and then cut Neeleman loose. But the bulk of the book describes the development and success of JetBlue and presents a superficial look at some extremely troubling aspects of Neeleman’s business philosophy, such as his disdain for unions ("I think they did a great thing for our country at a certain time") and his allowing JetBlue to share records of five million passenger transactions (a violation of its own privacy policy) with an army contract company working on post-9/11 security problems, a decision Wynbrandt too easily explains as a product of Neeleman’s Mormon-based "respect for patriarchal authority."